Contributions of Imām Abū Hanīfah on Prophetic Hadīth: an analysis - Mohiuddin, Mohammad (Department of Qurʾan and Sunnah Studies, Kulliyyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS), 2023)
Imam Abū Hanīfah is considered one of the prominent scholars who contributed most to adhering to the spirit of revelation and authentic Prophetic practices, proven by his contributions to the consecration of Islamic Fiqh. Fiqh and Prophetic Hadiths are interdependent, so Sharī`ah rulings must be justified either by revelation, by Prophetic practices, or by analogy with the evidence of the two primary sources of Sharī`ah. Therefore, the works of Imam Abu Hanifah refer to the Quranic āyāt and the Hadiths of the Prophet (PBUH). The paper aims to analyse the works and contributions of Imam Abū Hanīfah on Prophetic Hadīth. Relying on the descriptive and analytical methods in this study, this paper explores some of the original contributions of Imam Abū Hanīfah, especially in transmitting and promoting the Hadīths of the Prophet (PBUH). This paper also responds to some misunderstandings, being an ongoing debate between experts who seem to have negative attitudes about factual facts and realities related to Imam Abū Hanīfah’s contributions to the history of the development of Prophetic Hadīths. This paper also responds to the severe criticism levelled against the actual image of Imam Abū Hanīfah by referring to quotations from Muslim scholars whose credibility and depth in the field of Prophetic Hadīth. throughout Islamic history have been accepted.